State regulation as a factor of social significance of China’s modern culture industry - L. V. Filindash (Вестник университета)
The article is based on the study of state-party normative documents, such as the National Cultural Development Plan, The Cultural Industries Reinvigoration Plan, the National Economic and Social Development Plans China’s National Economic and Social Development Plans for the Twelfth, Thirteenth and Fourteenth FiveYear Plan periods. The focus on cultural projects is understood as an instrument of China’s soft power in its foreign policy course. In addition, national projects of educational and cultural nature are given the importance of state branding in the system of global reforms undertaken in the country. The article considers such reasons for the authorities to address cultural issues as the inadequate system of services provided in the field of education and culture; the predominance of small-scale commodity production in the cultural industry. The lack of professionalism of the management of the cultural institutions has negative consequences for the cultural ecology. The tasks of state regulation are: improvement of general cultural characteristics of the population and society as a whole, economic growth, preservation of the environment, increase of material level of the population.